2020
DOI: 10.1155/2020/4749135
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancements in CD47 Signal Transduction Pathways Involved in Vascular Diseases

Abstract: Cardiovascular and cerebrovascular diseases caused by atherosclerosis have a high disability rate and reduce the quality of life of the population. Therefore, understanding the mechanism of atherosclerosis and its control may interfere with the progression of atherosclerosis and thus control the occurrence of diseases closely related to atherosclerosis. TSP-1 is a factor that has been found to have an antiangiogenic effect, and CD47, as the receptor of TSP-1, can participate in the regulation of antiangiogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…CD47 acts as a "do not eat me" receptor by interacting with SIRPα on the healthy macrophage surface membrane and prevents phagocytosis by triggering a dephosphorylation cascade [7][8][9]. Vascular growth factor (VEGF) and its receptor (VEGFR2) can be activated by TSP-1 and CD47 in combination to stimulate angiogenesis, and the interaction between CD47 and integrin αVβ3 enhances neovascularization to allow tumor growth [10]. Studies have shown that the overall survival (OS) and progression-free survival (PFS) of DLBCL patients, especially those with the activated B-cell-like (ABC) subtype, are significantly reduced when both CD47 on tumor cells and SIRPα in stromal cells are upregulated or when only SIRPα expression is increased.…”
Section: Applications Of Cd47 In Clinical Therapiesmentioning
confidence: 99%
“…CD47 acts as a "do not eat me" receptor by interacting with SIRPα on the healthy macrophage surface membrane and prevents phagocytosis by triggering a dephosphorylation cascade [7][8][9]. Vascular growth factor (VEGF) and its receptor (VEGFR2) can be activated by TSP-1 and CD47 in combination to stimulate angiogenesis, and the interaction between CD47 and integrin αVβ3 enhances neovascularization to allow tumor growth [10]. Studies have shown that the overall survival (OS) and progression-free survival (PFS) of DLBCL patients, especially those with the activated B-cell-like (ABC) subtype, are significantly reduced when both CD47 on tumor cells and SIRPα in stromal cells are upregulated or when only SIRPα expression is increased.…”
Section: Applications Of Cd47 In Clinical Therapiesmentioning
confidence: 99%
“…CD47 is a “don't eat me signal” on the cell surface and is involved in a range of cellular processes, including apoptosis , proliferation , adhesion , and migration . 26 EndoV is shown to cleave RNA at inosines, and the high expression of CD47 in the EndoV −/− mice could be attributed to a lack of transcript degradation in the absence of ENDOV. However, inspection of adenosine‐to‐inosine editing (observed as Adenosine to Guanine mutations) in the RNA sequencing data when compared with the mouse genomic sequence (GRCm38.p6, Ensembl release 98) 18 in the CD47 transcript showed no adenosine‐to‐inosine editing in either wild‐type or EndoV −/− mRNA (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“… 116 , 117 Plaque cells highly express an antiphagocytosis ligand, Cluster of Differentiation 47 (CD47), on their surfaces, which inhibits them from being cleared by efferocytosis. 118 In fact, mice treated with anti-CD47 antibodies restored efferocytosis and prevented atherosclerosis. 119 However, these mice also developed anemia due to the antibody’s effects of off-target clearance of red blood cells in the spleen.…”
Section: Emerging Anti-atherosclerotic Therapiesmentioning
confidence: 99%